Women’s contribution to the deconstruction of xixth-century scientific-medical discourse misogyny - Iglesias Aparicio, Pilar (Filanderas, 2020)
For the last four decades, a great number of studies have been published about the construction of xixth century scientific-medical discourse about women’s bodies, health and sexuality, which presented women as weak and sick beings, dependent on their sexual organs and physiological functions, so proving their natural inferiority. The obsessive pursuit of the relationship between brain and female sexual organs and the sexual difference in mind functions reinforced the rejection to women’s access to higher education. The impossibility of women to access universities and other scientific institutions, facilitated that the voice of scientific-medical knowledge was mostly male. However, the xixth century women’s movement promoted women’s access to knowledge and professional practice. This paper shows some women scientists’ contribution to the deconstruction of the misogynistic hegemonic discourse, mainly Elizabeth Garrett and Mary Putnam, MD.
Keywords: Scientific-medical Discourse; XIXth Century; Sexual Difference; Mental Health; Neurosexism